The Effect of Kinesio Taping in the Ankle Sprains of Athletes - Mehdi Ghorbani; Bijan Goodarzi (The Society of Aging and Physical Activity (SAPA), 2017)
Objectives. The purpose of this study was the importance of applying Kinesio tape (KT) in relieving the pain in athletes' ankles using Y balance test and star. Methods. 22 male athletes with average age of 22.33±1.37 were discussed with and without Kinesio tape. At first athletes didn't use kinesiology tape on their deltoid ligament and did the (Y) balance test in 3 directions, then star twirling test (SEBT) in 8 directions that focused on the center of one plexus. These tests were repeated 3 times and all the stages of them were recovered after 24 hours and then the tests done on a pad and on a solid surface. Results. Athletes in both tests on a soft pad experienced a high pressure on their muscles according to the position of their leg in plantar and dorsiflexion state;and they couldn't finish the test. Conclusion. The test showed that the Kinesio tape on a soft surface (pad) did have any positive effects on the muscles.